PENGEMBANGAN PERANGKAT PEMBELAJARAN BIOLOGI SEKOLAH MENENGAH PERTAMA BERORIENTASI INKUIRI PADA MATERI ORGANISASI KEHIDUPAN - Diyyan Marneli (Inovasi Pendidikan, 2017)
Biology is one subjects taught at school which required student to have a good understanding on abstract concepts. Based on Local-Based Curriculum, a teacher should be able to develop a learning set which was suitable with the condition of the school. Therefore, the researcher was interested in developing an inquiry-based learning set in Biology on Life Organization topics which was valid, practical and effective.This was a developmental research which used 4D (four D) models that consisted of defining, designing, developing and disseminating. In this research, the disseminating phase was not done. The data gotten in this research was validated by three scientists and two practitioners. Furthermore, the data was tried out to the first year student in group 6 (class VII6) at SMP Negeri 2 Kota Solok.The result of the research showed that the inquiry-based learning set which had been develop which consisted of Lesson Plan, learning materials, Worksheet and Evaluation instruments was valid. Based of the application of the learning set in teaching and learning process, and student and teachers responses on it, the learning set developed was very practical. The learning set was also effective. In addition, student learning achievement and their psychomotor score were in a good category. Key word: development, learning equipment, inquiry